Hydralazine protects the heart against acute ischaemia/reperfusion injury by inhibiting Drp1-mediated mitochondrial fission. Issue 1 (2nd January 2021) - Kalkhoran, Siavash Beikoghli; Kriston-Vizi, Janos; Hernandez-Resendiz, Sauri; Crespo-Avilan, Gustavo E; Rosdah, Ayeshah A; Lees, Jarmon G; Costa, Joana Rodrigues Simoes Da; Ling, Naomi X Y; Holien, Jessica K; Samangouei, Parisa; Chinda, Kroekkiat; Yap, En Ping; et al.
Abstract: Aims: Genetic and pharmacological inhibition of mitochondrial fission induced by acute myocardial ischaemia/reperfusion injury (IRI) has been shown to reduce myocardial infarct size. The clinically used anti-hypertensive and heart failure medication, hydralazine, is known to have anti-oxidant and anti-apoptotic effects. Here, we investigated whether hydralazine confers acute cardioprotection by inhibiting Drp1-mediated mitochondrial fission. Methods and results: Pre-treatment with hydralazine was shown to inhibit both mitochondrial fission and mitochondrial membrane depolarisation induced by oxidative stress in HeLa cells. In mouse embryonic fibroblasts (MEFs), pre-treatment with hydralazine attenuated mitochondrial fission and cell death induced by oxidative stress, but this effect was absent in MEFs deficient in the mitochondrial fission protein, Drp1. Molecular docking and surface plasmon resonance studies demonstrated binding of hydralazine to the GTPase domain of the mitochondrial fission protein, Drp1 (KD 8.6±1.0 µM), and inhibition of Drp1 GTPase activity in a dose-dependent manner. In isolated adult murine cardiomyocytes subjected to simulated IRI, hydralazine inhibited mitochondrial fission, preserved mitochondrial fusion events, and reduced cardiomyocyte death (hydralazine 24.7±2.5% vs. control 34.1±1.5%, P =0.0012). In ex vivo perfused murine hearts subjected to acute IRI, pre-treatment with hydralazine reduced myocardial infarct size (as % left ventricle: hydralazine 29.6±6.5% vs. vehicle control 54.1±4.9%, P =0.0083), and in the murine heart subjected to in vivo IRI, the administration of hydralazine at reperfusion, decreased myocardial infarct size (as % area-at-risk: hydralazine 28.9±3.0% vs. vehicle control 58.2±3.8%, P <0.001). Conclusion: We show that, in addition to its antioxidant and anti-apoptotic effects, hydralazine, confers acute cardioprotection by inhibiting IRI-induced mitochondrial fission, raising the possibility of repurposing hydralazine as a novel cardioprotective therapy for improving post-infarction outcomes.